Contingency Table Analyses of the Bride-Price Practice in Marriage: A Case Study of Shikhar Metropolitan Area-1 Kapallekee in Far-Western Nepal - Malla, Ganesh B.; Malla, Sarojin B.; Malla, Hira C.; Uprety, Mina D. (Nepalese Journal of Statistics, 2024)
Background: The socio-cultural fabric of Nepalese society is deeply intertwined with traditional marriage practices, which are influenced by various factors, including parental economic status and education. Previous studies suggest that these elements significantly affect the types of marriages individuals experience, particularly in rural settings where customs and financial considerations dictate marital arrangements. This study seeks to explore these dynamics to better understand how parents’ socio-economic conditions shape their children’s marriage choices. Objective: The primary objective of this research is to empirically examine the interplay between marriage types—Bride Price and Kanyadaan—and various socio-economic factors within a rural Nepalese context. Specifically, the study aims to analyze how respondents' socio-economic characteristics, including their parents' educational attainment and economic status, influence the prevalence and distribution of these marriage practices. By identifying patterns and relationships among these variables, the study seeks to provide a deeper understanding of the cultural and economic drivers shaping marital traditions in the study population. Materials and Methods: The research employed a quantitative approach, utilizing structured questionnaires to gather data from 126 respondents in rural areas of Shikhar Metropolitan area 1 of Doti. The Contingency Table Method was conducted to examine the associations between types of marriage (bride price and Kanyadaan) and many socio-economic variables. Data were collected and analyzed to identify patterns and correlations that reflect the socio-economic influences on marriage practices. Results: This study explores the prevalence and determinants of two distinct marriage practices—Kanyadaan and Bride Price—in a diverse socio-cultural setting. Based on an analysis of 126 marriages, 38.1% were classified as Kanyadaan marriages, emphasizing spiritual bonds, while 61.9% followed the Bride Price practice, involving monetary transactions. The study reveals significant associations between marriage types and socio-demographic variables. Bride Price marriages were most common among Sudras (84.4%) and least prevalent among Brahmins (14.3%), highlighting jatis-based disparities (p < 0.001). Similarly, educational attainment emerged as a critical determinant, with Bride Price marriages declining from 84.72% among illiterate women to 0% among those with secondary education (p < 0.001). Occupation and economic status of parents also influenced marriage practices, with Bride Price marriages most prevalent among farmers (72.6%) and the poor economic class (100%), while less common among government employees (18.2%) and middle-class families (54%) (p < 0.01). Although temporal trends showed fluctuations in Bride Price prevalence, these were not statistically significant (p > 0.05). Overall, the findings underscore the role of education, jatis, and socio-economic factors in shaping marriage practices, with implications for understanding the persistence of traditional customs and their transformation in response to modernization.